Interpretation of modified glucose tolerance test among pregnant Malaysian women - Al-Kubaisi, Muna Khaleel Dheyab; Abdulrazzaq, Saad Mohammed; Win @ Fahmida, Nilar (International Journal of Innovative Research in Medical Science, 2020)
Aim: Is to find the mean and two standard deviation of the serum blood sugar among pregnant women while running the modified oral glucose tolerance test (MOGTT) as screening for gestational diabetes mellitus (GDM) & to compare the readings with other protocols adopted in diagnosing GDM. Method: A cross sectional study among pregnant women running routine MOGTT at 24-28 weeks’ gestation. A total of 149 women participated in 4 months period. The test included 5 ml of venous blood sample taken after fasting for 8 hours and a second blood sample 2 hours after having 200 ml of 75 g glucose solution within 10 minutes. Results: The mean for the fasting blood sugar is 4.32 mmol/L±0.52 making value of 2SD of 5.36 mmol/l. The mean of the 2 hours glucose level was .11mmol/l±1.38 making the 2SD value of 8.87 mmol/l. Conclusion: Our results for the 1st reading in MOGTT is near to the value of the local protocol in diagnosing GDM. The 2 hours postprandial reading in the local protocol is fairly low when compared with our findings & with guidelines of nearby communities.